A STUDY OF FACTORS HINDERING ENGLISH SPEAKING AMONG LOWER SECONDARY STUDENTS IN THE NONG LUANG SCHOOL GROUP, LAN KRABUE DISTRICT, KAMPHAENG PHET PROVINCE - Dilokpornchaikul, Nunnapachsorn; Adipat, Surattana (Journal of Educational Review Faculty of Education in MCU, 2025)
This study aimed to investigate the factors impeding the development of English-speaking skills among lower secondary students (Mathayomsuksa 1–3) in the Nong Luang School Group, Lan Krabue District, Kamphaeng Phet Province. The sa mple group consisted of 80 Mathayomsuksa 1–3 students from schools in the Nong Luang School Group, Lan Krabue District, Kamphaeng Phet Province. The study was conducted using a survey research approach. The research instrument used in this study was a questionnaire. The research was conducted through the following procedures: analyzed a questionnaire focused on three principal domains: (1) learner-related factors, (2) instructional factors, and (3) learning environment factors. Analyze the research results using percentage, mean (M), and standard deviation (S.D.), and compare them with the predetermined criteria for interpretation. The assessment was based on a 5-point Likert scale. The research findings revealed that learner-related factors had the highest mean score, indicating a high level of impact. An analysis of individual items in this category found that the students' lack of self-confidence while speaking English received the highest mean score. The second highest category was learning environment factors, which yielded a moderate level of impact. An analysis of individual items in this category showed that the most prominent issue was the teaching approach, with most teachers employing grammar-translation methods rather than emphasizing English communication. Lastly, instructional factors were also found to have a moderate impact. The highest scoring item in this category indicated that students lacked opportunities to communicate in English with native speakers.